Safety and Efficacy of Different Therapeutic Interventions on Prevention and Treatment of COVID-19 - Gyanwali, Pradip; Sharma, Sitasma; Pant, Suman; Koirala, Pallavi; Adhikari, Kriti; Koirala, Janak; Dhimal, Meghnath (Journal of Nepal Health Research Council, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the strain of coronavirus that causes coronavirus disease 2019 (COVID-19), a respiratory illness. COVID-19 has now become a global public health crisis causing alarming numbers of morbidity and mortality. Ever since the COVID-19 pandemic started scientists, researchers, universities, companies, and institutions all around the world have been endeavoring to discover a potential treatment for COVID-19. Numerous studies and clinical trials on vaccines and drugs for the prevention and treatment of COVID-19 are underway across the world. However, the uncertainty around the efficacy and safety of various treatment regimens have become one of the biggest challenges in the battle against the SARS-CoV-2. This paper is a narrative review of articles regarding the various treatments and vaccines being tested for the SARS-CoV-2, available in the PubMed database along with Google Scholar. There are ongoing clinical trials on potential drugs such as remdesivir, favipiravir, lopinavir/ritonavir, chloroquine, and hydroxychloroquine, corticosteroids tocilizumab, azithromycin, anakinra, etc. and other therapeutic modalities like convalescent plasma therapy. Likewise, vaccines against SARS-CoV-2 are being developed and tested, including mRNA, non-replicating viral vector, DNA, protein subunit candidate vaccines, etc. Although some early-stage clinical trials and studies on these drugs and vaccines have shown positive results, definitive and conclusive results are yet to be obtained.Keywords: COVID-19; antiviral drugs; COVID-19 treatment; COVID-19 vaccine; SARS-CoV-2